2018
DOI: 10.1111/tpj.13980
|View full text |Cite
|
Sign up to set email alerts
|

NtTPN1: a RPP8‐like R gene required for Potato virus Y‐induced veinal necrosis in tobacco

Abstract: Potato virus Y (PVY) is one of the most damaging viruses of tobacco. In particular, aggressive necrotic strains (PVY ) lead to considerable losses in yield. The main source of resistance against PVY is linked to the va locus. However, va-overcoming PVY isolates inducing necrotic symptoms were observed in several countries. In this context, it is important to find va-independent protection strategies. In a previous study, the phenotyping of 162 tobacco varieties revealed 10 accessions that do not carry the va a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…Genes for proteases with caspase-like activity that are markers of cell death were induced, as were also endoplasmic reticulum chaperones, markers of the endoplasmic reticulum stress response [105] (Figure 2), which is a known consequence of intensive viral multiplication [101]. Similarly, in the symptomatic part of tobacco leaves infected with PVY, the concentrations of ROS and PR gene induction was the strongest and correlated with detected high concentrations of the virus [14].…”
Section: Sensitive Response: Too Late or Too Weakmentioning
confidence: 94%
See 3 more Smart Citations
“…Genes for proteases with caspase-like activity that are markers of cell death were induced, as were also endoplasmic reticulum chaperones, markers of the endoplasmic reticulum stress response [105] (Figure 2), which is a known consequence of intensive viral multiplication [101]. Similarly, in the symptomatic part of tobacco leaves infected with PVY, the concentrations of ROS and PR gene induction was the strongest and correlated with detected high concentrations of the virus [14].…”
Section: Sensitive Response: Too Late or Too Weakmentioning
confidence: 94%
“…PVY is recognized by the plant by receptor proteins also in susceptible interaction [14], triggering the immune response, but the response is not able to restrict the virus (Figure 2). Several studies comparing sensitive and resistant interaction showed the importance of timing for efficient defense response.…”
Section: Sensitive Response: Too Late or Too Weakmentioning
confidence: 99%
See 2 more Smart Citations
“…The total RNA was adjusted to 50 mg/mL and was reverse transcribed according to the manufacturer’s instructions using the RevertAid H Minus enzyme (Thermo Scientific) and oligo(dT) primers. The cDNA was used to perform the real‐time Q‐RT‐PCR on the Light Cycler 480 Instrument II (Roche, Bâle, Switzerland), using the Light Cycler ® 480 SYBR Green I MASTER Kit (Roche, Bâle, Switzerland) following the protocol described in Michel et al (). The PCR mix per well included 10 µL of Master mix, 0.6 µL of each primer (0.3 mM) eIF4E‐2 Fwd and eIF4E‐2 Rev (Table ), and 5 µL of cDNA.…”
Section: Methodsmentioning
confidence: 99%